Consolidated Position Statements: A Tabular Approach. - Vanasse, Robert W. (The Accounting Review, 1968)
This article focuses on designing consolidated position statements in a tabular format to make the study and teaching of accounting courses easier. By holding some factors constant and varying certain selected conditions-investment cost, percentage of ownership, and time it becomes possible to effectively illustrate some of the primary relationships between the selected conditions and the three special items of goodwill, minority interest, and retained earnings as they are presented in consolidated statements of financial position. The exercise provides twenty-four different sets of conditions. The necessary data can easily be mimeographed on a single page for classroom use in the following manner. The completed table can also be used for the purpose of reviewing the patterns of changes which take place in the position statement amounts as a result of changes in the selected conditions. This tabular approach helps the student recognize some of the primary relationships between investment cost, percentage of ownership, and time, and consolidated goodwill, minority interest, and consolidated retained earnings.